Transgender Youth in Romania: Psychological Challenges, Social Perceptions, and Evidence-Based Clinical Interventions - Sava, Nicu-Ionel; Popa, Brigitte; Lungu, Andreea (New Trends in Psychology, 2025)
This article explores the psychological challenges, social perceptions, and evidence-based interventions concerning transgender youth in Romania, a population facing heightened vulnerability due to stigma, discrimination, and limited access to affirming care. Addressing this topic is crucial for advancing clinical practice and educational policy in a context where public discourse remains polarized. While international research has extensively documented the mental health risks of transgender youth, including elevated rates of depression, anxiety, and suicidality (Olson et al., 2006; Turban et al., 2020), Romanian data remain scarce. This article builds on global literature while contextualizing findings within the cultural, legal, and social realities of Romania. The article employs a theoretical review combined with illustrative case vignettes based on clinical and educational observations. Sources were drawn from peer-reviewed literature, WHO guidelines, and WPATH standards of care. Findings highlight pervasive social stigma, lack of family and institutional support, and systemic barriers to healthcare access. Evidence-based interventions—such as gender-affirming psychotherapy, family counseling, and guided social transition—demonstrate positive outcomes for psychological well-being and resilience. This work provides a culturally adapted framework for clinicians, educators, and policymakers, advocating for inclusive mental health services and systemic reforms. It contributes to the limited Romanian literature on transgender youth, offering actionable recommendations for improving support and reducing risk.